Marketing Mix in an Effort to Maintain The Product GONG CHA on The Existence of International Sale of Beverage Products - Rizki Nurul Nugraha; Fauzi Achmad Riyadi (West Science Interdisciplinary Studies, 2024)
This research discusses the marketing mix in an effort to maintain Gong Cha products in the existence of sales of beverage products on an international scale with the aim of finding out whether the Gong Cha beverage brand applies a marketing mix in an effort to maintain its products on an international scale. This research uses a qualitative descriptive approach method to present a complete picture of gong cha products on an international scale. Research methods include observation and interviews with related parties, and documentation. And assisted by using Strength, Weakness, Opportunity and Challenge (SWOC) analysis to identify strengths, weaknesses, opportunities and threats in maintaining Gong Cha products on an international scale, especially in Indonesia, with the aim of maximizing strengths, minimizing weaknesses, and responding to challenges, and build opportunities in developing service businesses. The results of this research show that the Gong Cha beverage brand is able to maintain its products on an international scale. The findings in this research can help Gong Cha to maintain competition on an international scale, especially in Indonesia.